Dyslipidemia in Renal Dysfunction among Non-diabetic Individuals from the 2019 Indonesian Cohort Study: A Cross-Sectional Study - Retiaty, Fifi; Dany, Frans; Ernawati, Fitrah; Nurjanah, Nunung; Efriwati, Eriwati; Arifin, Aya Yuriestia; Sundari, Dian; Prihatini, Mutiara; Widoretno, Widoretno; Sahara, Ema; Imanningsih, Nelis; Herawati, Ade Nugraheni (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The aim of this study was to investigate the relationship between dyslipidemia and the estimated Glomerular Filtration Rate (eGFR) values in a healthy population without a history of diabetes mellitus. Data were part of the cohort study database of 2019. Data analysis was perfomed using descriptive and inferential statistics with linear regression in 893 of 1,545 non-diabetic participants. The results showed that the average cholesterol levels, High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), and triglycerides were 196.75, 48.71, 123.37, and 109.56 mg/dl, respectively, and the average eGFR level of the respondents was 98.47±15.50 mg/dl. This study found that age, HDL levels, and LDL levels had a significant relationship with eGFR (p<0.05). It was concluded that increasing age and LDL levels and decreasing HDL levels would decrease eGFR.